2009
DOI: 10.5021/ad.2009.21.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo-like Depigmentation Associated with Metastatic Melanoma of an Unknown Origin

Abstract: Although malignant melanoma usually occurs after the diagnosis of vitiligo-like depigmentation, the latter is rarely followed by the former. We herein report on such a case in which recognition of the vitiligo-like depigmentation preceded diagnosing the metastatic melanoma by several months. A 56-year-old woman had first developed vitiligo-like depigmentation on the forehead, eyelids, neck and back 18 months previously and thereafter she detected a hard mass in the left axilla 2 months previously. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…All those theories can explain the correlation between melanoma and vitiligo. The evidence supports that the presence of vitiligo may be a favorable prognostic factor for survival theoretically due to the immune mechanism responsible for melanocytic proliferation causing depigmentation of skin and spontaneous regression of primary melanoma which were reported [ 26 28 ]. One of the studies reported by Nordlund et al [ 28 ] showed that a 10-year survival rate among patients with nonmetastatic melanoma with vitiligo was 49%.…”
Section: Discussionsupporting
confidence: 82%
“…All those theories can explain the correlation between melanoma and vitiligo. The evidence supports that the presence of vitiligo may be a favorable prognostic factor for survival theoretically due to the immune mechanism responsible for melanocytic proliferation causing depigmentation of skin and spontaneous regression of primary melanoma which were reported [ 26 28 ]. One of the studies reported by Nordlund et al [ 28 ] showed that a 10-year survival rate among patients with nonmetastatic melanoma with vitiligo was 49%.…”
Section: Discussionsupporting
confidence: 82%
“…The development of leukoderma post treatment with IL-2 for melanoma has been previously reported (1)(2)(3)(4)(5). However the occurrence of leukoderma in association with newer immunomodulating drugs, such as vemurafenib and ipilimumab, has just recently been reported (6,7).…”
Section: Discussionmentioning
confidence: 95%
“…One of the known side-effects of immunotherapeutic agents for melanoma, such as interleukin-2 (IL-2), vemurafenib, and ipilimumab, is leukoderma; however leukoderma has also been associated with higher rates of metastatic melanoma, as well as preceding the detection of melanoma (1)(2)(3)(4)(5). Collectively, this phenomenon is called melanoma-associated leukoderma (MAL).…”
mentioning
confidence: 97%
“…Similar vitiligo-like depigmentation in malignant melanoma has been reported in literature. [ 8 9 ] It is postulated that depigmentation is due to immune-mediated response against antigens shared by normal melanocytes and melanoma cells by CD8+ T cells, thus resulting in destruction of normal melanocytes. [ 10 ] Our case was unique in having icthyotic scaling in addition to leukoderma-like lesions which is not reported in literature.…”
Section: Discussionmentioning
confidence: 99%